(untitled) (American Journal of Management, 2023)
The purpose of this research is to understand the urban characteristics of Tama New Town and develop a disaster-resistant community that aligns with those characteristics. This paper reports on the implementation of a “resident questionnaire on disaster prevention consciousness” among residents around Tama University, based on the Resilience Assessment Grid (RAG) concept used in Resilience Engineering. The RAG defines the four capabilities of a resilient organization as “Resilient Local residents = Anticipating + Watch over (Monitoring) + Preparation (Responding) + Learning.” We quantified the resilience potential of the community and found that Preparation (Responding) scored lower than the other items. Our findings can inform the design and management of a disaster-resistant community that is better prepared to anticipate, monitor, respond to, and learn from disasters.